THE INFLUENCE OF COMPETENCE, INNOVATION, MOTIVATION, AND JOB DESIGN ON THE PERFORMANCE OF CONSTRUCTION EXPERTS WITH CAREER DEVELOPMENT AS A MEDIATING VARIABLE IN WEST JAVA - Dody Kusmana; Bahtiar Usman; Deasy Aseanty (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study examines the influence of competence, innovation, motivation, and job design on the performance of construction experts, with career development as a mediating variable. The high rate of project delays, cost overruns, and declining quality highlights performance issues among construction experts in West Java. For this research, 140 experts affiliated with ASTEKINDO West Java were surveyed. SmartPLS 3.0 was employed to model Partial Least Squares-Structural Equation Modeling (PLS-SEM) for data analysis. The descriptive findings indicate that competence, innovation, motivation, job design, and career development fall within the “good to very good” category, although weaknesses remain in the dimensions of values, work targets, and career development opportunities. Hypothesis testing results show that innovation has a negative and insignificant effect on performance, while competence significantly influences career development. These findings underscore that improving the performance of construction experts requires a structured career development system, enhanced motivation, and adaptive job design